2023
DOI: 10.2147/iprp.s377635
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Good Pharmacy Practices by Community Pharmacies in Lebanon and Opportunities for Quality Improvement: It is Time to Act

Abstract: Purpose Good pharmacy practice is an important standard that highlight the quality of services in community pharmacies. In 2018, The Order of Pharmacists in Lebanon (OPL) published their own good pharmacy practices (GPP) guidelines. The need exists for investigational studies to assess GPP implementation status and the professional conduct of on-site staff towards these standards. Methods Data collection was carried out between February and August 2020 using a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…30 However, our study's findings were lower than those of a study on community pharmacies in Lebanon's compliance with GPP and areas for quality improvement, which revealed 88.6% had separate storage for expired pharmaceuticals. 3 While the current study showed a relatively high availability of distinct storage facilities, there may be opportunities for improvement based on the findings from other regions. By identifying areas for enhancement and learning from best practices in different settings, pharmacy facilities can strive to optimize their storage practices and infrastructure to better serve their patients and maintain regulatory compliance.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…30 However, our study's findings were lower than those of a study on community pharmacies in Lebanon's compliance with GPP and areas for quality improvement, which revealed 88.6% had separate storage for expired pharmaceuticals. 3 While the current study showed a relatively high availability of distinct storage facilities, there may be opportunities for improvement based on the findings from other regions. By identifying areas for enhancement and learning from best practices in different settings, pharmacy facilities can strive to optimize their storage practices and infrastructure to better serve their patients and maintain regulatory compliance.…”
mentioning
confidence: 67%
“…2 A successful healthcare system is built on sound pharmacy practices, and associated standards emphasize the value of pharmacy services and the role of the pharmacist in enhancing patient health. 3 Dispensing is performed by a wide range of individuals with a wide range of backgrounds and training, which plays a crucial role in the realization of rational drug therapy based on the principle of good dispensing practices (GDP). 4 It refers to giving the appropriate medication and medical supplies to the appropriate patient in the necessary dosage and quantity in a package that preserves acceptable potency and quality for a predetermined amount of time, along with clear drug information for implementing rational drug therapy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations